2020
DOI: 10.1515/cclm-2020-0273
|View full text |Cite
|
Sign up to set email alerts
|

Exact time of venous blood sample collection – an unresolved issue, on behalf of the European Federation for Clinical Chemistry and Laboratory Medicine (EFLM) Working Group for Preanalytical Phase (WG-PRE)

Abstract: AbstractObjectivesAn accurate knowledge of blood collection times is crucial for verifying the stability of laboratory analytes. We therefore aimed to (i) assess if and how this information is collected throughout Europe and (ii) provide a list of potentially available solutions.Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Decreased clotting time in the presence of rEcarin is an important advantage in blood collection since attention has been drawn to the unreliability of sample collection and processing, which may impact on the stability of analytes [ 48 , 49 ]. For example, accurate registration of collection time is necessary for determining whether some tests should be performed or not (e.g., glucose, hormones, drug monitoring) [ 50 ]. We have shown that the quality of serum and analyte determination are unaffected by the inclusion of the snake venom prothrombin activator, OSPA [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased clotting time in the presence of rEcarin is an important advantage in blood collection since attention has been drawn to the unreliability of sample collection and processing, which may impact on the stability of analytes [ 48 , 49 ]. For example, accurate registration of collection time is necessary for determining whether some tests should be performed or not (e.g., glucose, hormones, drug monitoring) [ 50 ]. We have shown that the quality of serum and analyte determination are unaffected by the inclusion of the snake venom prothrombin activator, OSPA [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sub-clause 5.4.4.2 f) of ISO 15189 specifies that, when needed, the sample collection time is recorded. However, according to a survey carried out by the European Federation of Clinical Chemistry and Laboratory Medicine (EFLM) in 2017, this is not homogeneously addressed by laboratories in Europe (von Meyer et al, 2020). On the other hand, it was realised that standardised protocols for patient preparation (fasting) for laboratory examination were lacking (Simundic et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone may adsorb separating gel in a few days if left in tubes [26]. Parameter stability finally can be influenced by fundamental elements such as time of collection and transportation conditions from collecting point to the laboratory [28]. A new sample is required and should be monitored to ensure a valid analysis if a preanalytical error is recognized earlier before the analytical phase [27].…”
Section: Introductionmentioning
confidence: 99%